2018
DOI: 10.1016/j.jalz.2018.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the impact of sex and gender in Alzheimer's disease: A call to action

Abstract: The exclusion of sex and gender has impeded faster advancement in the detection, treatment, and care of AD across the clinical spectrum. Greater attention to these differences will improve outcomes for both sexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
415
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 546 publications
(477 citation statements)
references
References 148 publications
13
415
5
1
Order By: Relevance
“…Women have a greater lifetime risk of developing AD, which is not fully explained by greater longevity. 26 Despite the well-described differences in risk of hearing loss between men and women, published studies have not reported whether the association between hearing loss and cognitive decline varies by sex. A recent American Geriatrics Society and National Institute on Aging Conference recommended that in future studies "data need to be stratified according to sex."…”
Section: Introductionmentioning
confidence: 99%
“…Women have a greater lifetime risk of developing AD, which is not fully explained by greater longevity. 26 Despite the well-described differences in risk of hearing loss between men and women, published studies have not reported whether the association between hearing loss and cognitive decline varies by sex. A recent American Geriatrics Society and National Institute on Aging Conference recommended that in future studies "data need to be stratified according to sex."…”
Section: Introductionmentioning
confidence: 99%
“…These seemingly contradictory research findings point to significant gaps in our understanding of the effects of estrogen on brain function [8,9]. Many of these knowledge gaps were recently highlighted by the think tank convened by the Women's Alzheimer's Research Initiative [9] and the Society for Women's Health Research Interdisciplinary Network on AD expert panel [8]. These include the need to better understand how estrogen influences risk at the molecular level [8], the need to resolve discrepancies between animal models and human clinical trials [8,9], the need to understand the role of progesterone [9], and the need to better understand how APOE confers female‐biased risk [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…However, the overall outcomes are controversial due to the findings of the Women's Health Initiative Memory Study (WHIMS) which showed that HRT increased the risk for dementia [29,30]. These seemingly contradictory research findings point to significant gaps in our understanding of the effects of estrogen on brain function [8,9]. Many of these knowledge gaps were recently highlighted by the think tank convened by the Women's Alzheimer's Research Initiative [9] and the Society for Women's Health Research Interdisciplinary Network on AD expert panel [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sex may modulate not only the prevalence of risk factors for cognitive impairment and AD but also the susceptibility to the effects of risk factors (for a review, see previous works). We found that poorer TICS‐m score was associated with male sex while there was no sex difference in education, age, or APOE ε4 status.…”
Section: Discussionmentioning
confidence: 99%